Enhancement of ionic conduction in alginate–PVA polymer electrolytes doped with ammonium thiocyanate - Nurul Aqilah, Wahab; Saadiah, M. A.; N. F., Mazuki; N. M., Ghazali; Aoki, K.; Nagao, Y.; Ahmad Salihin, Samsudin (Springer, 2025)
This study explores the eco-friendly enhancement of ionic conduction properties and transport properties in solid polymer electrolytes (SPEs) based on a sustainable alginate (Al) and polyvinyl alcohol (PVA) blend, modified by varying weight percentages (wt%) of ammonium thiocyanate (NH4SCN) using a solution casting technique. The SPE system was characterized using Fourier-transform infrared (FTIR) spectroscopy, Thermal gravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM), and electrical impedance spectroscopy (EIS). SEM images revealed significant modifications in surface morphology correlating with different NH4SCN contents. FTIR analysis confirmed interactions between the alginate–PVA matrix and NH4SCN, evidenced by shifts and changes in peak intensities resulting from the protonation of H ⁺ -OOC. Impedance studies indicated a reduction in bulk resistance (Rb) with increasing NH4SCN content up to 35 wt%, achieving the highest ionic conductivity of 3.4 × 10⁻ 4 S cm⁻ 1 at room temperature. Temperature dependence studies revealed that the SPE systems adhere to Arrhenius behavior, with regression values nearing unity. Additionally, dielectric response analysis showed a consistent trend with ionic conductivity, indicating enhanced transport properties. These findings highlight the potential of alginate–PVA–NH4SCN SPEs for use in environmentally friendly applications such as proton batteries and supercapacitors, offering a sustainable alternative in energy storage solutions.